Vitamin D deficiency and iron deficiency anemia - M Hosseini; S Esmailzade; R Hashemi; M Sepandi; K Parastouei; T Babashamsi; M Taghdir; MR Naghii (فصلنامه ابن سینا)
Background: Vitamin D deficiency (VDD) and iron deficiency anemia (IDA) are the most common nutritional deficiencies among infants, children, and women around the world. The purpose of this article was to provide an overview of observational and clinical trial studies have been conducted on the effects of deficiency and improvement of vitamin D and iron.